Войств почвенного покрова бурлинского района (кнгкм) западно-казахстанской области - Мендыбаев, Е.Х. (Изд-во КарГУ им. Е.А.Букетова, 2010)
Мақалада 2002 жылғы біздің экспедициямыз жинаған вегетациялық кезеңдегі зерттеу мəліметтері ұсынылады. Қара-қоныр жəне шалғынды-қоныр топырақтағы гумус, азот жəне фосфордың құрамы берілген. Топырақ жамылғысындағы ауыр металдар жəне коэффициент концентрациясының талдау нəтижелері көрсетілген. Зерттелген топырақтағы Pb, Zn, Cu, Mn мөлшері ШМК-дан аспайды, ал Сd 1,4-5,4, Ni-22, Со-1,4-5,0 — артық. Materials are put in a basis of the present work collected by us during forwarding researches in a current of the vegetative period of 2002 given the maintenance гумуса, nitrogen and phosphorus in dark-kashtanoyh and lugovo-chestnut soils. Results of the analysis of a soil cover on heavy metals and concentration factor are resulted. Maintenance Pb, Zn, Cu, Mn in investigated soils does not exceed PDK (ПДК) and Сd exceeds maximum concentration limit from 1,4 to 5,4 times; quantity Ni in 22 times, With from 1,4 to 5,0 times.